2021
DOI: 10.1242/dev.196212
|View full text |Cite
|
Sign up to set email alerts
|

Tsga8 is required for spermatid morphogenesis and male fertility in mice

Abstract: During spermatogenesis, intricate gene expression is coordinately regulated by epigenetic modifiers, which are required for differentiation of spermatogonial stem cells (SSCs) contained among undifferentiated spermatogonia. We previously found that KMT2B conveys H3K4me3 at bivalent and monovalent promoters in undifferentiated spermatogonia. Because these genes are expressed late in spermatogenesis or during embryogenesis, we expect that many of them are potentially programmed by KMT2B for future expression. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Recently, Kobayashi et al . [ 22 ] revealed that Tsga8 is required for spermatid morphogenesis in mice. Although no clear orthologs of mouse Tsga8 have been found in other mammalian species, a highly divergent hypothetical gene has been identified within the genomic region containing the rat dystrophin gene [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kobayashi et al . [ 22 ] revealed that Tsga8 is required for spermatid morphogenesis in mice. Although no clear orthologs of mouse Tsga8 have been found in other mammalian species, a highly divergent hypothetical gene has been identified within the genomic region containing the rat dystrophin gene [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kobayashi et al . [ 22 ] previously established the crucial role of mouse Tsga8 , a putative ortholog of rat Dtsp , in spermiogenesis, particularly in proper spermatid morphogenesis. The testicular phenotype exhibited by BMD rats closely mirrors that of Tsga8 -deficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the intra-and inter-molecular disulfide crosslinks formed by cysteine residues in PRM1, the characteristic toroidal structures are created and each contains roughly 50 kb of DNAs. This binding between PRM1, PRM2 and DNA backbone leads to the remarkable compression of approximately 85% of chromatins which are finally stored in the sperm head, and a small proportion of histones is retained which plays important roles after fertilization (32)(33)(34). These processes guarantee the unharmed transferring of the paternal genetic information to the oocyte and assure that the genetic information can be properly accessed by the developing embryo (1).…”
Section: Pre-fertilization Stagementioning
confidence: 99%
“…Radiotherapy is an effective treatment for many tumours. About 60% of patients with newly diagnosed cancers have radiotherapy as their first-line treatment (Kobayashi et al, 2021). Radiotherapy can significantly improve survival in cancer patients and the survival of children with cancer has increased to 84% due to the emergence of effective cancer therapy (Karim-Kos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%